(untitled) - Chapman, Stephen (New Jersey, 1998)
The book considers the definition of environment to include preservation and protection of natural resources, and regulations aaffecting all elements of the environment. It is organized into five general subject areas: General concepts; Natural resource regulation; Pollution control; Waste and waste management; and Pesticide safety, food safety, and personal issues.
Keywords: Environmental law,Environmental policy; United States,United States